Percutaneous trans-tracheal endoscope assisted excision of thoracic tracheal tumour in a four-year-old child in an emergency setting - Karan Aggarwal; Smriti Panda; Kapil Sikka; Chirom Amit Singh; Aswin Chandran (Elsevier, 2021)
Patients with lower thoracic tracheal obstruction arising as a result of neoplasms most commonly present in the hospital emergency. These pathologies are rare and the therapeutic options are also limited. We present a case of a four year old male with a lower thoracic tracheal tumor who presented to us in casualty with stridor and respiratory distress. A unique management approach employing the use of transtracheal endoscopy is described.